2013
DOI: 10.1002/lary.23744
|View full text |Cite
|
Sign up to set email alerts
|

Voice conversion in cochlear implantation

Abstract: Objectives/Hypothesis Voice conversion algorithms may benefit cochlear implant (CI) users who better understand speech produced by one talker than by another. It is unclear how the source or target talker's fundamental frequency (F0) information may contribute to perception of converted speech. This study evaluated voice conversion algorithms for CI users in which the source or target talker's F0 was included in the converted speech. Study Design Development and evaluation of computerized voice conversion al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…This may be partly due to poor representation and/or perception of voice characteristics. Previous studies have shown that CI users' gender categorization performance is highly variable and generally poorer than that of NH listeners (Fu et al 2004(Fu et al , 2005Balaban 2009, 2010;Massida et al 2013;Wilkinson et al 2013). It was argued in these studies that CI users might rely more on F0 than NH listeners.…”
Section: Introductionmentioning
confidence: 97%
“…This may be partly due to poor representation and/or perception of voice characteristics. Previous studies have shown that CI users' gender categorization performance is highly variable and generally poorer than that of NH listeners (Fu et al 2004(Fu et al , 2005Balaban 2009, 2010;Massida et al 2013;Wilkinson et al 2013). It was argued in these studies that CI users might rely more on F0 than NH listeners.…”
Section: Introductionmentioning
confidence: 97%
“…However, as the signal delivered in each electrode is modulated by the speech envelope that carries temporal F 0 cues, pitch perception remains limitedly possible. Studies on gender categorization, another task that relies on the perception of temporal and spectral cues of a speaker’s voice, confirmed that CI users mostly rely on temporal voice pitch cues, whereas NH listeners can utilize both spectral and temporal voice pitch cues (Fu, Chinchilla, & Galvin, 2004; Fu, Chinchilla, Nogaki, & Galvin, 2005; Fuller, Gaudrain, et al., 2014; Kovacic & Balaban, 2009, 2010; Wilkinson, Abdel-Hamid, Galvin, Jiang, & Fu, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Some studies set out to examine whether certain forms of speech would affect talker perception. These studies found that CI users were better at picking up on indexical information when presented with neutral speech (compared to whispered speech; Hazrati et al, 2015), speech presented through broadband (compared to presented through the telephone; Horng et al, 2007), and with original stimuli (compared to F0 manipulated speech; Wilkinson et al, 2013). These studies highlight how different real-life situations might impact talker perception for CI users.…”
Section: Task Characteristicsmentioning
confidence: 92%